2019
DOI: 10.1182/blood.2019001880
|View full text |Cite|
|
Sign up to set email alerts
|

The whole-genome landscape of Burkitt lymphoma subtypes

Abstract: Key Points We investigated all 3 subtypes of BL by WGS and transcriptome sequencing. Experimental validation through CRISPR screening and mouse models provides a better functional understanding of BL genetic drivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
114
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 30 publications
4
114
0
1
Order By: Relevance
“…Of pathological relevance to BL, TCF4 encodes the helix-loop-helix transcription factor 4 reported to interact with ID3, which is inactivated by recurrent mutations in up to two-thirds of BL [6,7,15]. Somatic TCF4 deregulation has been implicated as an alternative mechanism of ID3-inactivating or TCF3activating mutations in BL [6,15]. Our somatic WES analysis showed that both patients lacked mutations in ID3 and TCF3.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Of pathological relevance to BL, TCF4 encodes the helix-loop-helix transcription factor 4 reported to interact with ID3, which is inactivated by recurrent mutations in up to two-thirds of BL [6,7,15]. Somatic TCF4 deregulation has been implicated as an alternative mechanism of ID3-inactivating or TCF3activating mutations in BL [6,15]. Our somatic WES analysis showed that both patients lacked mutations in ID3 and TCF3.…”
mentioning
confidence: 93%
“…Of interest, the rs374301928-TCF4 locus appears to have been subject to early negative selection among vertebrate species and archaic hominins that may be indicative of relevant regulatory function [14]. Of pathological relevance to BL, TCF4 encodes the helix-loop-helix transcription factor 4 reported to interact with ID3, which is inactivated by recurrent mutations in up to two-thirds of BL [6,7,15]. Somatic TCF4 deregulation has been implicated as an alternative mechanism of ID3-inactivating or TCF3activating mutations in BL [6,15].…”
mentioning
confidence: 99%
“…[1][2][3] Genotypically, BL shows a translocation of MYC with the IG heavy or, less frequently, IG light chain genes, a simple karyotype, and a mutational spectrum distinct from that of other aggressive B-cell lymphomas, with common alterations of ID3, TCF3, CCND3, 4 and others. 5 BM infiltration is common, occurring in 30% of patients, so the BM is frequently the first site of biopsy. Some cases present with BM and peripheral blood (PB) involvement only, and these are referred to as Burkitt leukaemia.…”
Section: Blmentioning
confidence: 99%
“…Alberto Zam o 1,2 Peter Johnston 3 Ayoma D Attygalle 4 Camille Laurent 5 Daniel A Arber 6 Falko Fend 7…”
Section: Acknowledgementsunclassified
“…Acute lymphoblastic leukemia (ALL) is the most common type of leukemia, and is characterized by uncontrolled proliferation of immature lymphoid cells [1,2]. Despite signi cant advances over the past few decades to develop treatments for ALL, ~25% of children and half of the adults do not respond to chemotherapy or relapse [3][4][5].…”
Section: Introductionmentioning
confidence: 99%